Altered effective connectivity between lateral occipital cortex and superior parietal lobule contributes to manipulability-related modulation of the Ebbinghaus illusion. (February 2022) - Chen, Lihong; Zhu, Shengnan; Feng, Bengang; Zhang, Xue; Jiang, Yi
Abstract: Action and perception interact reciprocally in our daily life. Previous studies have found that object manipulability can affect visual perceptual processing. Here we probed the neural mechanisms underlying the manipulability-related modulation effect using the well-known Ebbinghaus illusion with the central circle replaced by a high (i.e., a basketball) or a low (i.e., a watermelon) manipulable object. Participants ( N = 30) were required to adjust the size of a comparison circle to match that of the central object in the Ebbinghaus configuration. The results showed that the perceived illusion magnitude for the basketball target was significantly reduced than that for the watermelon target, and the manipulability-related modulation effect was manifested in self-connections in the left primary visual cortex and the left superior parietal lobule (SPL), as well as reciprocal connections between the left lateral occipital cortex (LOC) and SPL. Notably, the disparity of the illusion magnitude between the watermelon and the basketball target was positively correlated with the extrinsic connectivity from the left LOC to SPL. The findings suggest that object manipulability can modulate the Ebbinghaus illusion, likely through accentuating the high-manipulability object along the visual processing streams. Moreover, they provide clear evidence that manipulability-related modulation of visual perception relies on the functional interactions between the ventral and dorsal visual pathways.